Use of computer-integrated technologies of designing in foundry - Сапегина, Елена Николаевна (Technology audit and production reserves, 2012)
The results of mathematical modeling of shrinkage and formation of shrink defects in the moulded body parts, using a variety of materials and structural components of foundry equipment, are given in the article.